1984
DOI: 10.1007/bf00283653
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein: a trigger of insulin-dependent diabetes in the BB rat?

Abstract: Animals from a colony of spontaneously diabetic insulin-dependent BB rats were fed from weaning with semi-synthetic diets in which natural proteins were replaced by l-amino acids with or without the addition of either milk or wheat proteins. The normal 50% incidence of diabetes in the colony was reduced to 15% in rats fed the basic semi-synthetic diet, while it was 35% and 52% when supplemented with gluten or milk, respectively. Thus, dietary factors might precipitate the expression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
90
1
7

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(104 citation statements)
references
References 1 publication
4
90
1
7
Order By: Relevance
“…A detailed study of infant feeding patterns indicated that the age at introduction of dairy products had the closest association with the risk of IDDM when the duration of both overall and exclusive breast-feeding was taken into account [8]. This is in accordance with previous studies [9,10] which showed that the early introduction of dairy products increased the incidence of diabetes in diabetes-prone Bio Breeding rats. Further, increased levels of antibodies to cow's milk formula, BLG and BSA have been observed in newly-diagnosed diabetic children [5,[11][12][13].…”
supporting
confidence: 87%
“…A detailed study of infant feeding patterns indicated that the age at introduction of dairy products had the closest association with the risk of IDDM when the duration of both overall and exclusive breast-feeding was taken into account [8]. This is in accordance with previous studies [9,10] which showed that the early introduction of dairy products increased the incidence of diabetes in diabetes-prone Bio Breeding rats. Further, increased levels of antibodies to cow's milk formula, BLG and BSA have been observed in newly-diagnosed diabetic children [5,[11][12][13].…”
supporting
confidence: 87%
“…Experiments in BB rats [16] and NOD mice [17] have clearly demonstrated a deleterious effect of various complex foreign-protein weaning diets in the disease process. The strongest indirect evidence in man for an association between early exposure to dietary CM proteins and the risk of type 1 diabetes comes from epidemiological studies of infant feeding, with an inverse correlation between the duration of breastfeeding and the incidence of type 1 diabetes in childhood (reviewed in [1][2][3]).…”
Section: Discussionmentioning
confidence: 99%
“…The relation between short duration of total breastfeeding and early exposure to cows' milk proteins with increased risk of Type I diabetes has been shown by a number of studies in humans [33] and in animal models [34,35]. Duration of breastfeeding also modulates, however, the incidence and prevalence of infections early in life.…”
mentioning
confidence: 99%